PENGARUH STRATEGI MEMBACA DIRECT READING THINKING ACTIVITY (DRTA) TERHADAP SISWA SEKOLAH DASAR - Otang Kurniaman; Eddy Noviana; Neni Hermita; Charlina Charlina (Universitas Negeri Medan, 2019)
Learning DRTA strategy is a suitable strategy in reading, so that research is conducted using a quasi-experiment method with nonequivalent group pretest-posttest design to see the effect seen from the pretest data in the experimental class of 10, 34, and the control class of 10.43 with an ideal score 20. In the posttest data, the average experimental class is 15.22, and the control class is 13.5, seen from the results of the pretest and posttest data, the experimental class has a higher increase in comprehension reading ability. To be clearer whether there is a difference in the ability of elementary school students, it was first tested by calculating the t-test statistic on pretest data = 0.13 ≤ = 2.00 it can be concluded that there is no significant difference. Posttest data in the t-test is obtained = 1.79 ≤ = 2.00 it can be concluded that there is no significant difference. So it can be concluded that this study has an influence on the DRTA strategy seen in the increase in the average pretest and posttest data of elementary school students.Keywords: Strategy DRTA, Elementary School Students, Nonequivalent Group